Involvement of mTOR in Type 2 CRF Receptor Inhibition of Insulin Signaling in Muscle Cells - Chao, Hongxia (Mol Endocrinol, 2015)
Type 2 corticotropin-releasing factor receptor (CRFR2) is expressed in skeletal muscle and stimulation of the receptor has been shown to inhibit the effect of insulin on glucose uptake in muscle cells. Currently, little is known about the mechanisms underlying this process. In this study, we first showed that both in vivo and in vitro CRFR2 expression in muscle was closely correlated with insulin sensitivity, with elevated receptor levels observed in insulin resistant muscle cells. Stimulation of CRFR2 by urocortin 2 (Ucn 2), a CRFR2-selective ligand, in C2C12 myotubes greatly attenuated insulin-induced glucose uptake. The inhibitory effect of CRFR2 signaling required cAMP production and is involved the mammalian target of rapamycine pathway, as rapamycin reversed the inhibitory effect of CRFR2 stimulation on insulin-induced glucose uptake. Moreover, stimulation of CRFR2 failed to inhibit glucose uptake in muscle cells induced by platelet-derived growth factor, which, similar to insulin, signals through Akt-mediated pathway but is independently of insulin receptor substrate (IRS) proteins to promote glucose uptake. This result argues that CRFR2 signaling modulates insulin's action likely at the levels of IRS. Consistent with this notion, Ucn 2 reduced insulin-induced tyrosine phosphorylation of IRS-1, and treatment with rapamycin reversed the inhibitory effect of Ucn 2 on IRS-1 and Akt phosphorylation. In conclusion, the inhibitory effect of CRFR2 signaling on insulin action is mediated by cAMP in a mammalian target of rapamycine-dependent manner, and IRS-1 is a key nodal point where CRFR2 signaling modulates insulin-stimulated glucose uptake in muscle cells.